2021
DOI: 10.1002/rth2.12621
|View full text |Cite
|
Sign up to set email alerts
|

Generic PROMIS item banks in adults with hemophilia for patient‐reported outcome assessment: Feasibility, measurement properties, and relevance

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…When investigated, floor and ceiling effects were found in less than 2% of stroke patients. Only on the PROMIS pain interference short forms, 31-36% had the lowest score, similar to the 26% found in adults with hemophilia reported by Kuijlaars et al [29], but this does not have to indicate lack of validity because these patients may just have no pain. No studies were found that examined content validity, criterion validity and cross-cultural validity/measurement invariance in stroke populations.…”
Section: Discussionsupporting
confidence: 82%
“…When investigated, floor and ceiling effects were found in less than 2% of stroke patients. Only on the PROMIS pain interference short forms, 31-36% had the lowest score, similar to the 26% found in adults with hemophilia reported by Kuijlaars et al [29], but this does not have to indicate lack of validity because these patients may just have no pain. No studies were found that examined content validity, criterion validity and cross-cultural validity/measurement invariance in stroke populations.…”
Section: Discussionsupporting
confidence: 82%
“…To solve issues like lengthy questionnaires, another development in the field of haemophilia is the introduction of generic Patient Reported Outcomes Measurement Information System (PROMIS) item banks. In adults, the PROMIS Computer Adaptive Test (CAT) ‘physical function’ was demonstrated to be a feasible, reliable and valid alternative to the HAL full for PWH, with a low number of items (mean number of items was 6.0) which is even lower than the 18 items of the HAL short 25 . However, before implementation of PROMIS CATs in day‐to‐day care and research several issues need to be addressed like good IT facilities for digital administration of CATs, clear visual feedback and cut‐off scores which helps in interpreting, monitoring and discussing individual items or scores, and budget for using CATs 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Joint status will be measured by physical examination (Haemophilia Joint Health Score),26–28 ultrasound (if available, according to the Haemophilia Early Arthropathy Detection with Ultrasound (HEAD US) score) 29. HR-QoL will be assessed with EQ5D(Y)-3L,30–32 and PROMIS (Patient-Reported Outcomes Measurement Information System) instruments (Physical Function/mobility and Pain Interference short forms) 33–35. Assessment of pain during emicizumab administration will be scored with the Visual Analogue Scale.…”
Section: Methods and Analysismentioning
confidence: 99%